PENERAPAN MODEL STAD DENGAN MEDIA DIGITAL WORD SQUARE UNTUK MENINGKATKAN PENGUASAAN KONSEP PADA KOMPETENSI DASAR UANG DAN LEMBAGA KEUANGAN - Taryadi Taryadi (Dinamika Pendidikan)
The Economics learning in SMP Nasima Semarang did not use an approach which involved students’ roles and potencies. Thus, it needs the STAD (Student Teams Achievement Division) learning model and Digital Word Square technique through class action research to solve the problem. The data showed that students’ activities such as motivation and activeness on the 1st cycle and 2nd cycle increased significantly. Whereas, the average of evaluation test result on the 1st cycle was 6.00 and rose to 8.57 on the 2nd cycle. It increased up to 29.98%. Based on the data above, It can be seen that the STAD learning model and DigitalWord Square technique was effective to improve students’ competencies to understand the concept of Money and Banks for the 9th Grade of SMP Nasima’s Students in the academic year of 2011/2012.